Nanoparticle-loaded antibacterial composite hydrogel as well as preparation method and application thereof
By developing the antibacterial composite hydrogel of nanoparticles, the problem of dehydrating, adhesion, and anti -microorganic invasion effects when the existing dressing is treated with chronic wounds in diabetes. dressing.
Patent Information
- Application Number
- CN202411501451.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Existing wound dressings have problems such as water loss, adhesion, and poor anti-microbial invasion when treating chronic wounds of diabetes, which is difficult to meet the multiple needs of wound healing.
Antibacterial composite hydrogels with load nanoparticles have been developed. Through the phenyl -borne -connecting methyl acrylated collagen and methyl acomitride polyinine as the substrate, add glucose oxidase and load core shell Nanozymes are prepared to prepare water gel carriers through optical curing linkage.
This hydrogel integrates multi -functional antibacterial, anti -inflammatory, antioxidant, and promoting new blood vessels. It can quickly respond to the special micro -environment of diabetic wounds, promote healing, reduce ROS levels, reduce blood sugar, generate H2O2 and glucose acid, promote mature collagen The formation of formation and the deposition of fibroblasts.
Smart Images

Figure CN119367589A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of pharmaceutical preparations, and in particular to an antibacterial composite hydrogel loaded with nanoparticles, and a preparation method and application thereof. Background Art
[0002] The persistent challenge of chronic wound nonhealing has been a significant burden on healthcare, and such wounds are common in patients with diabetes. This has greatly increased the financial and medical costs of global healthcare systems, ranging from $9.9 billion to $35.8 billion per year. It has specific characteristics, including persistent inflammation, impaired cell proliferation, impaired angiogenesis, increased susceptibility to infection and changes in the extracellular matrix, with amputation required in about 20% of cases. Patients with diabetes are particularly susceptible to these problems during the healing process. Debridement is currently the most common method for treating diabetic wounds. Debridement involves the removal of dead, damaged or infected tissue, thereby improving the healing potential of the remaining healthy tissue. Another important wound care method after surgery and systemic care is local treatment. There are many local treatments available for the treatment of diabetic foot wounds, including gauze, hydrogels, hydrocolloids, alginate dressings, foam dressings, silver ion dressings, dressings containing growth factors, silicon-impregnated non-invasive dressings, hyperbaric oxygen therapy, etc. Among them, the method of using dressings for treatment has received widespread attention in recent years. Dressing actually refers to a type of material used to cover, fill and heal wounds. As an effective treatment method, it can reduce the risk of patients' wounds being exposed to the outside world and becoming infected.
[0003] Gauze is still widely used in clinical practice as a traditional dressing. However, as people study wounds, they find that this dry dressing is very easy to lose water and adhere to the wound site, which can easily cause discomfort to patients when changing it, and the effect of gauze in preventing microbial invasion is poor. Translucent film dressings can promote wound healing, but due to their limited absorption capacity, they can only be used for shallow wounds with a small amount of exudate, but not for highly exudated wounds. Foam dressings also have the disadvantages of needing to be prepared with a specific thickness to absorb exudate, relying on specific polymer materials, not being easy to remove from the wound, and having a relatively single function, which limits their application in wound healing. The hydrophilicity of hydrocolloid dressings enables them to handle a certain amount of wound exudate, but high exudate will cause the dressing to separate from the wound surface; at the same time, the preparation of hydrocolloid dressings has greater restrictions on materials, which limits its scope of use to only chronic wounds containing mild exudate. Therefore, wound dressings that are more suitable for chronic wounds need to be developed urgently.
[0004] An ideal wound dressing should have the following characteristics: (1) sterile, easy to use, and low cost; (2) able to maintain a moist wound healing environment; (3) able to absorb excess wound exudate; (4) non-adhesive, non-toxic, and non-allergenic; (5) prevent foreign matter from contaminating the wound; (6) protect the wound from microbial invasion; (7) allow the exchange of internal wound gas with the outside world; and (8) provide thermal insulation and certain mechanical protection.
[0005] Compared with other commonly used dressings, hydrogel dressings have the advantages of reducing wound exudate, providing a moist environment, ensuring gas exchange, having a modulus that matches human soft tissue, and reducing patient pain during replacement, while also reducing restrictions on materials. Summary of the invention
[0006] In order to overcome at least one of the problems existing in the above-mentioned existing technologies, the present invention has developed a novel antibacterial composite hydrogel loaded with nanoparticles, which is based on phenylboronic acid grafted methacryloyl-type I collagen (rCol1MA-PBA) and methacryloyl-polylysine (EPLMA), to which glucose oxidase (GOx) is added as a pH regulating component, and the hydrogel carrier is prepared by photocuring cross-linking, and the core-shell nanozyme (C@Z@T) is loaded, which can spontaneously activate the production and clearance function of ROS, balance the homeostasis of ROS, and promote diabetic wound healing.
[0007] On the one hand, the present invention provides an antibacterial composite hydrogel loaded with nanoparticles, wherein the hydrogel network body is composed of phenylboronic acid grafted methacryloyl type I collagen rCol1MA-PBA and methacryloyl polylysine EPLMA, and cross-linked with glucose oxidase GOx, and is loaded with core-shell nanozyme C@Z@T, wherein the core-shell nanozyme C@Z@T is composed of a spherical CeO2 nanoparticle core and a zeolite imidazolate framework material TIF-8 shell, and tannic acid TA coated on the shell.
[0008] Furthermore, the hydrogel contains 10wt%-20wt% rCol1MA-PBA, 7.5wt%-12.5wt% EPLMA, 10mg / mL GOx, and 50-200μg / mL C@Z@T.
[0009] Furthermore, the rCol1MA-PBA is obtained by mixing 3-aminophenylboronic acid, EDC, NHS and type I recombinant collagen at room temperature; the 3-aminophenylboronic acid: EDC: NHS: type I recombinant collagen = 1.0 g: 1.0 g: 0.5 g: 2 g.
[0010] Furthermore, the EPLMA is prepared by nucleophilic amination ring-opening reaction of polylysine EPL and polymethyl methacrylate MA, and the molar ratio of MA to EPL is 11:1.
[0011] Furthermore, the particle size of the core-shell nanozyme C@Z@T is 20-700 nm, and the zeta potential is -26.9±0.721 mV.
[0012] Furthermore, the preparation method of the core-shell nanozyme C@Z@T comprises the steps of:
[0013] S1 Preparation of CeO2@ZIF-8 nanoparticles;
[0014] The spherical CeO2 nanoparticles and PVP are respectively dissolved in an organic solvent and mixed evenly, and then the product is immediately dispersed in a 2-methylimidazole / organic solvent solution after centrifugation until it is completely mixed; then, zinc salt is added, mixed and reacted to obtain the CeO2@ZIF-8 nanoparticles;
[0015] Preparation of S2 CeO2@ZIF-8@TA nanozyme;
[0016] The prepared CeO2@ZIF-8 nanoparticles are dispersed evenly in water, and then tannic acid is added to disperse evenly, and then centrifugally washed and dried to obtain the core-shell nanozyme.
[0017] Furthermore, in the step S1, the reaction temperature is 24-37°C, spherical CeO2 nanoparticles: PVP = 30-40mg: 0.5-1.5g; in the step S2, the reaction temperature is 25-35°C, CeO2@ZIF-8 nanoparticles: tannic acid = 0.1-0.5g: 0.05-0.15g.
[0018] Another aspect of the present invention further provides a method for preparing the antibacterial composite hydrogel, comprising the following steps:
[0019] A solution containing a photoinitiator is prepared, and then rCol1MA-PBA and EPLMA are dissolved therein. After they are completely dissolved, GOx is added and vortexed to completely dissolve and evenly disperse them. Subsequently, C@Z@T core-shell nanozymes are added and stirred to disperse. Then, cross-linking is performed under ultraviolet light under vacuum conditions to obtain the antibacterial composite hydrogel.
[0020] The photoinitiator may be a water-soluble photoinitiator commonly used in hydrogels, such as LAP, NAP, etc. The added amount is determined according to the specific type of photoinitiator.
[0021] Another aspect of the present invention also provides the use of the antibacterial composite hydrogel in wound dressings.
[0022] Furthermore, since the glucose oxidase (GOx) loaded in the hydrogel of the present invention can quickly respond to the special microenvironment of diabetic wounds, it can exert cascade enzyme catalytic activity, consume blood sugar in the wound site to generate H2O2 and gluconic acid. In addition, the core-shell nanozyme C@Z@T decomposes in an acidic microenvironment, generates O2, removes ROS, promotes the formation of mature collagen and the deposition of fibroblasts, and is therefore particularly suitable for diabetic wound dressings.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1) The raw materials of the hydrogel of the present invention are easy to obtain, the preparation method is simple, the price is low, and the ingredients are safe and reliable;
[0025] 2) Compared with traditional single-function wound healing materials, the hydrogel of the present invention integrates multiple functions such as antibacterial, anti-inflammatory, antioxidant and angiogenesis promotion, providing a more comprehensive therapeutic effect;
[0026] 3) The hydrogel of the present invention is loaded with glucose oxidase (GOx), which can quickly respond to the special microenvironment of diabetic wounds, exert cascade enzyme catalytic activity, and consume blood glucose in the wound site to generate H2O2 and gluconic acid.
[0027] 4) The hydrogel of the present invention can generate O2 in a slightly acidic environment under pH response, remove ROS, promote the formation of mature collagen and the deposition of fibroblasts, thereby accelerating the healing of diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is the NMR spectrum of the synthesized rCol1MA-PBA;
[0029] Figure 2 is the NMR spectrum of the synthesized EPLMA;
[0030] Figure 3 TEM image of the core-shell nanozyme C@Z@T;
[0031] Figure 4 This is the particle size distribution diagram of core-shell nanozyme C@Z@T;
[0032] Figure 5 is the Zeta potential of CeO2, ZIF-8, C@Z, and C@Z@T nanoparticles;
[0033] Figure 6 This is a composite hydrogel gelation diagram of an embodiment of the present invention;
[0034] Figure 7 This is a SEM image of the composite hydrogel according to an embodiment of the present invention. DETAILED DESCRIPTION
[0035] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings and specific embodiments. Preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0036] In the description of the present invention, unless otherwise clearly defined, terms such as heating, cleaning, weighing, freezing, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention in combination with the specific content of the technical solution.
[0037] In the description of the present invention, the description with reference to the terms "some embodiments", "examples", etc. means that the specific methods and materials described in conjunction with the embodiments or examples are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific methods and materials described can be combined in any one or more embodiments or examples in a suitable manner.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0039] In the following examples and comparative examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0040] Examples 1-6
[0041] This embodiment provides an antibacterial composite hydrogel loaded with nanoparticles, wherein the hydrogel network body is composed of phenylboronic acid grafted methacryloyl type I collagen rCol1MA-PBA and methacryloyl polylysine EPLMA, and cross-linked with glucose oxidase GOx, and is loaded with core-shell nanozyme C@Z@T, which is composed of a spherical CeO2 nanoparticle core and a zeolite imidazolate framework material ZIF-8 shell, and tannic acid TA coated on the shell.
[0042] Specifically, the preparation method comprises the steps of:
[0043] 1) Dissolve LAP in PBS buffer or physiological saline to form an aqueous solution with a mass fraction of 0.2%.
[0044] 2) Then use 0.2% LAP aqueous solution to dissolve rCol1MA-PBA and EPLMA, and after ultrasonication to completely dissolve them, add GOx and vortex for 10 minutes to completely dissolve and evenly mix them in the solution. Then add C@Z@T nanozyme and stir magnetically at 600 rpm for 10 minutes to evenly disperse the microspheres in the solution. Finally, pour it into the mold, remove bubbles under -1 bar vacuum, irradiate with 365nm wavelength ultraviolet light for 30 seconds to complete crosslinking, and demold to obtain the hydrogel.
[0045] The preparation methods of methacrylylated type I collagen rCol1MA-PBA, methacrylylated polylysine EPLMA, and core-shell nanozyme C@Z@T used in the examples are as follows:
[0046] (1) Preparation of phenylboronic acid grafted methacryloyl type I collagen (rCol1MA-PBA)
[0047] First, dissolve 2g of type I recombinant collagen in 100mL of water and stir until completely dissolved. Dissolve 1.0g of 3-aminophenylboronic acid, 1.0g of EDC and 0.5g of NHS in 50mL of water and 10mL of DMSO solution, and then add the mixture to the type I recombinant collagen solution. React at room temperature for 3 days, dialyze with a 3500Da dialysis bag, and lyophilize to obtain rCol1-PBA. Weigh 1.0grCol1-PBA and dissolve it in 100mL of deionized water. After fully dissolved, add 1mL of methacrylic anhydride, react at room temperature for 4h, dialyze with an 8000Da dialysis bag, and lyophilize to obtain rCol1MA-PBA.
[0048] Figure 1 The NMR spectrum of the synthesized rCol1MA-PBA shows characteristic peaks of the benzene ring on phenylboronic acid at 7.74, 7.53, and 7.41 ppm, indicating that rCol1-PBA was successfully synthesized. After methacryloylation, characteristic peaks of the vinyl group on the methacryloyl group appeared at 5.68 and 5.40 ppm, indicating that rCol1MA-PBA was successfully synthesized.
[0049] (2) Preparation of methacryloyl polylysine (EPLMA)
[0050] EPLMA was prepared by nucleophilic amination ring-opening reaction between EPL and MA. Specifically, EPL was dissolved in deionized water under stirring at 25°C for 2 hours to obtain a 10wt% solution. MA was added dropwise to the prepared EPL solution by mechanical stirring at 80°C and reacted for 6 hours until the oily liquid disappeared. The molar ratio of MA to EPL was 11:1. After the reaction, the obtained solution was filtered and dialyzed with a dialysis bag (1000Da) for 4 days. Finally, the obtained EPLMA solution was freeze-dried for 48 hours. The freeze-dried EPLMA powder was stored at -20°C for subsequent use.
[0051] Figure 2 This is the NMR spectrum of the synthesized EPLMA. The results show that: EPLMA has characteristic peaks of methacrylate vinyl (δ=5.62 and 5.40 ppm) and methyl (δ=1.8 ppm), indicating that lysine has been successfully modified.
[0052] (3) Preparation of core-shell nanozyme C@Z@T
[0053] 3.1 Preparation of spherical CeO2
[0054] Add 2g of cerium nitrate hexahydrate to 80mL of ethylene glycol, add 4mL of ultrapure water, and stir vigorously at room temperature for 30min. Transfer the mixed solution to a polytetrafluoroethylene-lined container, seal the stainless steel crystallization reactor with a lid, and perform hydrothermal synthesis at 180℃ for 8h. Centrifuge, wash repeatedly with ultrapure water, and then dry in an oven at 110℃ overnight. Grind the solid into powder, place it in a muffle furnace, heat it to 500℃ in air at a heating rate of 2℃ / min, and calcine it for 6h.
[0055] 3.2 Preparation of CeO2@ZIF-8 nanoparticles
[0056] CeO2 nanoparticles (35 mg) and PVP (1 g) were dissolved in methanol (50 mL) and then mixed at 25 ° C for 24 h. The product was immediately redispersed in 50 ml of 25.6 mM 2-methylimidazole (methanol solvent) after centrifugation and stirred at 25 ° C for 20 min until completely mixed. Subsequently, we added Zn(NO3)2·6H2O (50 mL of 25.2 mM methanol solvent) and mixed for another 30 minutes until the reaction was complete to produce the product. The final product was centrifuged at 12,000 rpm, purified with methanol three times, and vacuum dried to obtain CeO2@ZIF-8 nanoparticles, denoted as C@Z.
[0057] 3.3 Preparation of CeO2@ZIF-8@TA core-shell nanozymes
[0058] 0.3 g of the prepared CeO2@ZIF-8 was added to 100 mL of water and stirred for 30 min to make it uniformly dispersed. 0.1 g of tannic acid (TA) was added to the solution, stirred at 30 ° C for 10 min, centrifuged to obtain the precipitate, and washed with deionized water several times to remove the residual TA. Then, the wet CeO2@ZIF-8@TA nanoparticles were dried at 60 ° C for 12 h to obtain CeO2@ZIF-8@TA core-shell nanozyme, recorded as C@Z@T.
[0059] (4) Preparation of ZIF-8 nanoparticles
[0060] 3.3 g of 2-methylimidazole was dissolved in 70 mL of methanol solution to form solution A. Then 1.5 g of zinc nitrate hexahydrate was dissolved in 70 mL of methanol solution to form solution B. Solution A was slowly added to solution B to form a mixed solution, which was stirred at room temperature for 24 h and centrifuged. The obtained solid was washed three times with methanol solution and dried at 80°C overnight. The obtained sample was recorded as ZIF-8.
[0061] Figure 3 This is the transmission electron microscopy image of the prepared C@Z@T core-shell nanozyme. It can be seen that since the core cerium oxide is spherical, the obtained C@Z@T nanoparticles also present a uniform spherical shape and uniform size. Figure 4 Figure 3 is the particle size distribution of C@Z@T core-shell nanozyme. It can be seen that the particle size is between 20-700nm, and the average particle size is 214±8.246nm.
[0062] Figure 5 The Zeta potential statistics of CeO2 and ZIF-8 nanoparticles, C@Z, and C@Z@T nanoparticles show that the potentials of CeO2 and ZIF-8 nanoparticles are -7.56±1.58mV and 23.8±1.65mV, respectively. Due to the negative charge of tannic acid, the whole exhibits a negative charge, and the synthesized C@Z@T Zeta potential is significantly increased to -26.9±0.721mV, which indicates that the electrostatic repulsion between particles increases, the stability is significantly improved, and the core-shell nanozyme has good dispersibility.
[0063] Comparative Example 1
[0064] This comparative example provides a hydrogel, the main body of the hydrogel network is composed of phenylboronic acid grafted methacryloylated type I collagen rCol1MA-PBA, cross-linked with glucose oxidase GOx, and loaded with core-shell nanozyme C@Z@T. The core-shell nanozyme C@Z@T is composed of a spherical CeO2 nanoparticle core and a zeolite imidazolate skeleton material shell, and tannic acid coated on the shell.
[0065] The only difference from Example 1 is that in step 2), rCol1MA-PBA is dissolved with 0.2% LAP aqueous solution, and the rest is the same as Example 1.
[0066] Comparative Example 2
[0067] This comparative example provides a hydrogel, the main body of the hydrogel network is formed by cross-linking phenylboronic acid-grafted methacryloyl type I collagen rCol1MA-PBA, and is loaded with core-shell nanozyme C@Z@T. The core-shell nanozyme C@Z@T is composed of a spherical CeO2 nanoparticle core and a zeolite imidazolate skeleton material shell, and tannic acid coated on the shell.
[0068] The difference from Example 3 is that in step 2), there is no step of adding GOx, and the rest is the same as Example 3.
[0069] Comparative Example 3
[0070] This comparative example provides a hydrogel composed of phenylboronic acid grafted methacryloyl type I collagen rCol1MA-PBA and methacryloyl polylysine EPLMA.
[0071] The difference from Example 3 is that step 1) is omitted, and in step 2), rCol1MA-PBA and EPLMA are directly dissolved in water, and there is no step of adding GoX. The rest is the same as Example 3.
[0072] Since the solution does not contain photocrosslinking agent, direct ultraviolet light irradiation cannot crosslink to form a gel network.
[0073] Comparative Example 4
[0074] This comparative example provides a hydrogel, wherein the main body of the hydrogel network is made of methacrylylated polylysine EPLMA and cross-linked with glucose oxidase GOx.
[0075] The difference from Example 3 is that in step 2), 0.2% LAP aqueous solution is used to dissolve EPLMA, and there is no step of adding C@Z@T nanoparticles. The rest is the same as Example 3.
[0076] Comparative Example 5
[0077] This embodiment provides a hydrogel, wherein the main body of the hydrogel network is formed by cross-linking phenylboronic acid-grafted methacrylylated type I collagen rCol1MA-PBA and methacrylylated polylysine EPLMA.
[0078] The difference from Example 3 is that in step 2), there is no step of adding C@Z@T nanoparticles and GOx, and the rest is the same as Example 3.
[0079] The hydrogel formulations of various embodiments and comparative examples are shown in Table 1.
[0080] Table 1 Hydrogel formula of examples and comparative examples
[0081]
[0082]
[0083] Analysis of hydrogel effects:
[0084] 1. Analysis of hydrogel storage modulus
[0085] Table 2 Hydrogel storage modulus
[0086]
[0087] Note: Comparative Example 3 is liquid and was not tested.
[0088] Storage modulus test method: De-mold a cylindrical hydrogel sample with a liquid volume of 400 μL. Place it on a stainless steel parallel plate rotor with a diameter of 25 mm for rheological measurement. The test instrument is a rotational rheometer, the test temperature is 37°C, and the scanning strain is 1%. G' characterizes the elastic modulus of the sample.
[0089] The results show that the storage modulus of the hydrogel is mainly affected by the concentration of the hydrogel substrate rCol1MA-PBA and EPLMA. The higher the concentration of rCol1MA-PBA and EPLMA, the higher the storage modulus. The addition of GOx and C@Z@T will not have much effect on its storage modulus. In comparative example 3, if LAP is not added, the hydrogel cannot be photocured to form a hydrogel, and the storage modulus test cannot be performed.
[0090] 2. Analysis of hydrogel swelling properties
[0091] Table 3 Hydrogel swelling rate and volume expansion ratio
[0092]
[0093] Note: Comparative Example 3 is liquid and was not tested.
[0094] Swelling rate test method: Place 400μL of hydrogel precursor solution in a 48-well plate and irradiate it with ultraviolet light to form a gel. Use a balance to weigh the weight of the material, which is recorded as M0. Place the sample material in PBS, and after swelling for 6 hours, quickly use filter paper to absorb the surface moisture, weigh and record the sample mass as Mw. The sample water absorption rate (X) is calculated according to the following formula: X(%) = (Mw-M0) / M0×100%. Volume expansion ratio test method: Weigh the weight of the hydrogel sample with a balance, and use a vernier caliper to measure the diameter and height of the dressing. Place the measured sample material in distilled water, swell to equilibrium (6h), quickly use filter paper to absorb the surface moisture, and measure the diameter and height of the dressing after absorbing water. The water absorption expansion rate of the dressing is calculated as follows: VR(%) = (D1 2 ×H1) / (D0 2 ×H0)×100%, where D0 and D1 are the diameters of the sponge before and after absorbing water, respectively; H0 and H1 are the heights of the hydrogel before and after absorbing water, respectively, and the unit is mm.
[0095] The results show that the swelling rate and volume expansion ratio of the hydrogel are affected by EPLMA. The higher the EPLMA content, the higher the swelling rate and the larger the volume expansion ratio. The addition of GOx and C@Z@T has little effect on the swelling rate and volume expansion ratio.
[0096] 3. Analysis of hydrogel hemolysis rate
[0097] Table 4 Hydrogel hemolysis rate
[0098]
[0099] Note: Comparative Example 3 is liquid and was not tested.
[0100] Hemolysis rate test method: First, fresh whole blood is centrifuged at 2000rpm for 15min to remove serum. Repeat washing with PBS 5 times to ensure that pure red blood cells are obtained. The pure red blood cells are diluted with PBS solution to obtain a red blood cell suspension with a concentration of 2% (v / v). Then 1ml of the red blood cell suspension is added to the sample to be tested (100μL of gelled sample) and incubated at 37°C for 1h. After the mixture is centrifuged at 1600rpm for 10min, the absorbance value of the supernatant is measured at a wavelength of 524nm. In addition, distilled water is used as a positive control and PBS as a negative control. The calculation formula for the sponge hemolysis rate (H) is as follows: H(%) = (OD sample -OD negative ) / (OD positive -OD negative )×100, where H is hemolysis rate, unit: %; OD sample - Absorbance value of sample set; OD negative -Absorbance value of negative control group; OD positive-The absorbance value of the positive control group;.
[0101] The results show that the hemolysis rate of the hydrogel is less than 5%, which meets the requirements of biomedical materials. Since TA in C@Z@T nanoparticles has excellent antibacterial properties, it will also have a weak effect on red blood cells, but this is within a controllable range.
[0102] 4. Analysis of antibacterial properties of hydrogel
[0103] Table 5 In vitro antibacterial rate (%)
[0104]
[0105] Test method: Escherichia coli and Staphylococcus aureus were revived and cultured to the logarithmic growth phase, centrifuged, and the bacteria were collected and resuspended in physiological saline. The final bacterial solution concentration was 1×10 8 CFU / mL. After adding 500μL of the corresponding hydrogel solution to a 24-well plate, UV light was used to solidify the solution. 500μL of saline was added to the control group. Then 100μL of the diluted bacterial suspension and 1mL of sterile saline were added to each well, incubated at 37°C for 24 hours, and then spread on LB agar plates after gradient dilution and counted.
[0106] The results show that: EPLMA and C@Z@T work synergistically to exert a dual antibacterial effect with excellent results. In addition, rCol1MA-PBA is a protein and has no effect on killing bacteria. As an inherent antibacterial material, EPL has a broad-spectrum antibacterial activity against bacteria and fungi. The antibacterial activity of EPL is significantly reduced after grafting MA. Therefore, in the composite antibacterial hydrogel of the embodiment of the present invention, C@Z@T plays a major antibacterial role, and the higher the added amount, the stronger the antibacterial effect. This is mainly because ZIF-8 and TA in the core-shell nanozyme C@Z@T have good antibacterial activity, which will destroy the cell membrane structure of microorganisms, cause the interruption of cell material, energy and information transmission, and ultimately lead to cell death.
[0107] 5. Analysis of the antioxidant properties of hydrogels in vitro
[0108] Table 6 DPPH free radical scavenging rate (%)
[0109]
[0110] Test method: Prepare the sample according to the instructions of the commercially available DPPH free radical scavenging ability test kit, add the extract of the corresponding embodiment and comparative example to the DPPH solution, incubate in dark for 30 minutes, detect the absorbance at 515nm with a UV-visible spectrophotometer, and calculate the free radical scavenging rate.
[0111] The results show that the addition of C@Z@T further enhances the antioxidant effect of the hydrogel and gives the hydrogel the ability to scavenge free radicals. This is mainly because the TA molecular structure has multiple phenolic hydroxyl groups (-OH), which makes it have a strong hydrogen supply capacity, so it has outstanding antioxidant activity in scavenging free radicals.
[0112] It can be seen from the above results that the hydrogel samples of the embodiments of the present invention have better performance, especially the sample of embodiment 3. Figure 6 This is a schematic diagram of the composite hydrogel solidification into gel according to an embodiment of the present invention. Figure 7 This is the SEM image of the cured hydrogel. It can be seen that the cured hydrogel presents a three-dimensional network structure with uniform pores.
[0113] In the antibacterial composite hydrogel system of the present invention, the concentrations of rCol1MA-PBA and EPLMA mainly affect the storage modulus of the substrate, the swelling performance is mainly affected by EPLMA, EPLMA and C@Z@T work synergistically to exert a dual antibacterial effect, and the antioxidant performance is mainly affected by the addition of core-shell nanozymes. The components work together and support each other, have good antibacterial and antioxidant properties, and can be used for wound dressings, especially for diabetic chronic wounds.
[0114] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0115] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An antibacterial composite hydrogel loaded with nanoparticles, characterized in that: The hydrogel network body is composed of phenylboronic acid grafted methacryloyl type I collagen rCol1MA-PBA and methacryloyl polylysine EPLMA, and cross-linked with glucose oxidase GOx, and is loaded with core-shell nanozyme C@Z@T. The core-shell nanozyme C@Z@T is composed of a spherical CeO2 nanoparticle core and a zeolite imidazolate framework material ZIF-8 shell, and tannic acid TA coated on the shell.
2. The antibacterial composite hydrogel according to claim 1, characterized in that: The hydrogel contains 10wt%-20wt% rCol1MA-PBA, 7.5wt%-12.5wt% EPLMA, 10mg / mL GOx, and 50-200μg / mL C@Z@T.
3. The antibacterial composite hydrogel according to claim 1, characterized in that: The rCol1MA-PBA is obtained by mixing 3-aminophenylboronic acid, EDC, NHS and type I recombinant collagen at room temperature; the 3-aminophenylboronic acid: EDC: NHS: type I recombinant collagen = 1.0 g: 1.0 g: 0.5 g: 2 g.
4. The antibacterial composite hydrogel according to claim 1, characterized in that: The EPLMA is prepared by nucleophilic amination ring-opening reaction of polylysine EPL and polymethyl methacrylate MA, and the molar ratio of MA to EPL is 11:
1.
5. The antibacterial composite hydrogel according to claim 1, characterized in that: The particle size of the core-shell nanozyme C@Z@T is 20-700 nm, and the zeta potential is -26.9±0.721 mV.
6. The antibacterial composite hydrogel according to claim 5, characterized in that: The preparation method of the core-shell nanozyme C@Z@T comprises the following steps: S1 Preparation of CeO2@ZIF-8 nanoparticles; The spherical CeO2 nanoparticles and PVP are respectively dissolved in an organic solvent and mixed evenly, and then the product is immediately dispersed in a 2-methylimidazole / organic solvent solution after centrifugation until it is completely mixed; then, zinc salt is added, mixed and reacted to obtain the CeO2@ZIF-8 nanoparticles; Preparation of S2 CeO2@ZIF-8@TA nanozyme; The prepared CeO2@ZIF-8 nanoparticles are dispersed evenly in water, and then tannic acid is added to disperse evenly, and then centrifugally washed and dried to obtain the core-shell nanozyme.
7. The antibacterial composite hydrogel according to claim 6, characterized in that: In the step S1, the reaction temperature is 24-37°C, spherical CeO2 nanoparticles: PVP = 30-40mg: 0.5-1.5g; in the step S2, the reaction temperature is 25-35°C, CeO2@ZIF-8 nanoparticles: tannic acid = 0.1-0.5g: 0.05-0.15g.
8. The method for preparing the antibacterial composite hydrogel according to any one of claims 1 to 7, characterized in that: The steps include: A solution containing a photoinitiator is prepared, and then rCol1MA-PBA and EPLMA are dissolved therein. After they are completely dissolved, GOx is added and vortexed to completely dissolve and evenly disperse them. Subsequently, C@Z@T core-shell nanozymes are added and stirred to disperse. Then, cross-linking is performed under ultraviolet light under vacuum conditions to obtain the antibacterial composite hydrogel.
9. Use of the antibacterial composite hydrogel according to any one of claims 1 to 8 in wound dressings.
10. The use according to claim 9, wherein the wound dressing is a diabetic wound dressing.
Citation Information
Patent Citations
Peroxide nano-enzyme-glucose oxidase double-enzyme compound as well as preparation method and application thereof
CN114432459A
Nanoparticle with cascade enzyme catalytic activity and diabetes immunoregulation function and preparation and application of multifunctional hydrogel of nanoparticle
CN115957177A
Nano-enzyme with dual functions of resisting bacteria and removing excessive reactive oxygen species and preparation method of nano-enzyme
CN116019928A
Injectable antibacterial hydrogel for promoting healing of diabetes infected wound as well as preparation method and application of injectable antibacterial hydrogel
CN117085170A
Preparation method and application of AuNPs (at) MOF nano-enzyme with GOx, SOD and CAT three-enzyme cascade catalytic activity
CN118477099A
Cited By
Glucose response and population inhibition double-effect medicine, preparation method and application
CN120131922A
Photocuring hydrogel stent as well as preparation method and application thereof
CN121287907A
Photocured hydrogel scaffold and its preparation method and application
CN121287907B